Peran Strategis Indonesia dalam Penyelesaian Konflik Laut China Selatan dalam Perspektif Stabilitas Keamanan Regional - Toruan, Gerald Theodorus L. (Jurnal Keamanan Nasional, 2020)
The South China Sea Conflict has yet to be resolved, this conflict involves 4 ASEAN countries (the Philippines, Vietnam, Malaysia and Brunei Darussalam) as well as Taiwan and China. The South China Sea Conflict continues to escalate and can pose threats in the region. What’s more, the United States wants freedom of navigation in the South China Sea. The South China Sea Conflict entered a new phase in which the Philippines won a lawsuit in 2016 at the International Arbitration Court, which in essence did not recognizing the claims of the Chinese territory and the traditional fishing ground that China has always used as a proposition. This research is a qualitative descriptive study with the aim to formulate the role that can be taken by Indonesia in resolving the South China Sea conflict. The data collection technique is in-depth interviews with experts or observers of international relations. The results of the study are in the form of policy recommendations on the steps that must be taken in resolving the South China Sea conflict.